Vita Constantini: Who, When, Where - Długosz, Natalia (Poznańskie Studia Slawistyczne, 2022)
This review is a short presentation and an analysis of the book Кой, кога, къде в простарнното житие на св. Константин-Кирил (Vita Constantini: who, when, where) by Maya Ivanova and Tsvetomira Danova, published in 2021 in Sofia. The book consists of two main parts. The first and most extensive part is a kind of lexicon with 177 entries: personal name and by-names of actual historical figures; biblical and mythological characters; names of ethnonyms, tribes and languages; geographic names (including names of sacred objects), difficult and archaic words. Part II contains the text of the Vita. The book is a handbook intended for a wide group of lay audiences, including Bulgarian Studies scholars abroad. This handbook is a coherent and well-thought-out entity. The study combines the condition of scientific credibility with the feature of accessibility. There is a need for similar teaching aids in the didactic process of students of Slavic studies.